Relational memory and the hippocampus: Representations and methods - Konkel, Alex; Cohen, Neal J. (Frontiers in Neuroscience, 2009)
Since discovery of the importance of the hippocampus for normal memory, considerable research has endeavored to characterize the precise role played by the hippocampus. Previously we have offered the relational memory theory, which posits that the hippocampus forms representations of arbitrary or accidentally occurring relations among the constituent elements of experience. In a recent report we emphasized the role of the hippocampus in all manner of relations, supporting this claim with the finding that amnesic patients with hippocampal damage were similarly impaired on probes of memory for spatial, sequential, and associative relations. In this review we place these results in the context of the broader literature, including how different kinds of relational or source information are tested, and consider the importance of specifying hippocampal function in terms of the representations it supports.